"A river without water": Hydropolitics and the River Jordan in Palestinian literature. (June 2016) - Boast, Hannah
In this article I examine the representation of the River Jordan and ecological crisis in recent works by two of Palestine's best-known writers: the poem "A River Dies of Thirst" by Mahmoud Darwish, and Mourid Barghouti's memoir I Saw Ramallah . Ecocritics have paid scant attention to these writers' works, or to Palestinian literature in general; but the environment is a major domain of conflict between Israelis and Palestinians, and ownership of the River Jordan is a key source of tension, often discussed within the framework of "water wars". The River Jordan is currently in a highly degraded state due to pollution and the diversion of most of its waters by Israel. I examine the ways in which Darwish and Barghouti portray the Jordan's ecological decline as the outcome of Palestinian dispossession and Israeli occupation, suggesting that the texts form a literary counterpart to claims by Palestinian activists and solidarity groups of what Al Butmah and colleagues termed an "environmental Nakba". In particular, I build on Tricia Cusack's work on "riverscapes" and nationalism in order to draw out the different strategies used by both Darwish and Barghouti to express the impact of the loss of the River Jordan on Palestinian communities. While Darwish emphasizes the affective and communal consequences of Israel's exhaustion of the river, in a poem which can be read as an environmental analogue to Palestinian "memorial books", Barghouti stresses the links between hydropolitics and uneven development in the present day. I conclude with a caution about Darwish and Barghouti's shared reliance on an anthropocentric discourse of theft and ownership, which, I argue, ultimately facilitates unsustainable water use.